Innate immunity based cancer immunotherapy: B16-F10 murine melanoma model - Caisová, Veronika; Vieru, Andra; Kumžáková, Zuzana; Glaserová, Simona; Husníková, Hana; Vácová, Nikol; Krejčová, Gabriela; Paďouková, Lucie; Jochmanová, Ivana; Wolf, Katherine I; Chmelař, Jindřich; Kopecký, Jan; et al. (BMC cancer, 2016)
BACKGROUND: Using killed microorganisms or their parts to stimulate immunity for cancer treatment dates back to the end of 19th century. Since then, it undergone considerable development. Our novel approach binds ligands to the tumor cell surface, which stimulates tumor phagocytosis. The therapeutic effect is further amplified by simultaneous application of agonists of Toll-like receptors. We searched for ligands that induce both a strong therapeutic effect and are safe for humans. METHODS: B16-F10 murine melanoma model was used. For the stimulation of phagocytosis, mannan or N-formyl-methionyl-leucyl-phenylalanine, was covalently bound to tumor cells or attached using hydrophobic anchor. The following agonists of Toll-like receptors were studied: monophosphoryl lipid A (MPLA), imiquimod (R-837), resiquimod (R-848), poly(I:C), and heat killed Listeria monocytogenes. RESULTS: R-848 proved to be the most suitable Toll-like receptor agonist for our novel immunotherapeutic approach. In combination with covalently bound mannan, R-848 significantly reduced tumor growth. Adding poly(I:C) and L. monocytogenes resulted in complete recovery in 83% of mice and in their protection from the re-transplantation of melanoma cells. CONCLUSION: An efficient cancer treatment results from the combination of Toll-like receptor agonists and phagocytosis stimulating ligands bound to the tumor cells.
Keywords: melanom experimentální; infiltrace neutrofily; Phagocytosis; Respiratory Burst; ligandy; Melanoma; Resiquimod; Toll-Like Receptors; Immunity, Innate; cytokiny; Disease Models, Animal; respirační vzplanutí; Cancer immunotherapy; Neutrophils; Mice; Cytokines; poly I-C; fagocytóza; přirozená imunita; Neoplasms; Mannan; Neutrophil Infiltration; Ligands; modely nemocí na zvířatech; ženské pohlaví; toll-like receptory; imunoterapie; zvířata; Mannans; Innate immunity; nádory; neutrofily; Melanoma, Experimental; imidazoly; Poly I-C; myši; Immunotherapy; mannany; Female; Imidazoles; Animals